INTEGRATING RELIGIOUS MODERATION VALUES THROUGH EXTRACURRICULAR ACTIVITIES - Nurjani, Nurjani; Putri, Willa (Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study examines the effectiveness of the Arts and Scouts extracurricular programs in instilling the values of religious moderation to address the crisis of tolerance, exclusive grouping, and potential bullying among fifth-grade students at MIN 9 Aceh Tengah. Using a descriptive qualitative method, this research involved students, homeroom teachers, and instructors selected through purposive sampling. Data were collected through participant observation, interviews, and document analysis. The main findings indicate that the member randomization system (rolling groups) in the Scouts program compels students to collaborate across groups, thereby effectively instilling the values of tawazun (balance) and i'tidal (justice). Furthermore, the Arts extracurricular program was shown to foster tolerance (tasamuh) by honing emotional sensitivity and harmonization. The practical implications of this study confirm that integrating the values of religious moderation through extracurricular platforms successfully breaks down exclusive barriers, mitigates the risk of bullying, and fosters a harmonious madrasah culture.